A Mobile Application Based on Expert Judgment and their Influence on Investigations - Sánchez, Anthony (2020)
The technology used to solve traditional processes remains a great support that improves the research quality of university students. In this article, the level of influence that the use of a mobile application based on expert judgment would have will be evaluated in students of the last cycles of the Systems engineering career. In addition, the pre-experimental design, the Mobile - D methodology and the sample consists of thirty students from the last cycles of the career. The experimental group significantly improves the time it took to find an expert and validate research tools. You can also see the increased satisfaction of students and experts to perform the validation process. In conclusion, the expert judgment-based mobile app significantly improves the process of validating content instruments.